Development of a Multi-Epitope Peptide Vaccine Against Monkeypox Virus: Immunoinformatics Analysis for South East Asian HLA Alleles - Chandra, Nelson; Herdiansyah, Mochammad Aqilah; Kharisma, Viol Dhea; Ansori, Arif Nur Muhammad; Parikesit, Arli Aditya (Makara Journal of Science, 2025)
The monkeypox virus (MPXV), a DNA virus causing zoonotic disease, poses major global public health challenges, with mortality rates between 3%–6%. Although smallpox vaccines provide partial cross-protection, there is a critical need for a dedicated, effective monkeypox (mpox) vaccine. This study aimed to design a multi-epitope peptide-based vaccine specifically adapted to the HLA allele profiles common in Southeast Asian populations, where MPXV cases are rising. Using immunoinformatics, we screened for and detected B and T cell epitopes from the MPXV cell surface antigen and IFN-alpha/beta receptor proteins. The vaccine design was validated through a rigorous evaluation of its antigenicity, immunogenicity, allergenicity, and toxicity to ensure both safety and efficacy. Key epitopes were mapped to HLA alleles including HLA-A*11:01, HLA-A*24:02, and HLA-B*15:02, which are highly prevalent in Southeast Asia populations. Molecular docking analyses demonstrated stable interactions between the vaccine construct and TLR3/TLR4 immune receptors, suggesting a robust immune response activation. Additionally, molecular dynamics simulations confirmed the structural stability of the vaccine-receptor complex. This immunoinformatics-driven multi-epitope vaccine design offers a promising candidate for combating MPXV, with high projected coverage and immuno-genic potential for Southeast Asian populations. Validation in laboratory and clinical settings is recommended to con-firm these findings.